Association Between Metabolic Syndrome and Breast Cancer Risk: An Updated Meta-Analysis of Follow-Up Studies - Guo, Meng; Liu, Tingting; Li, Peiting; Wang, Tianying; Zeng, Chen; Yang, Meng; Li, Gang; Han, Jiang; Wu, Wei; Zhang, Ruopeng (Frontiers in Oncology, 2019)
Background: Association between metabolic syndrome (MetS) and incidence of breast cancer remains to be validated. Moreover, whether menopausal status of the women affects this association is unclear. A meta-analysis was performed to summarize the association between MetS and breast cancer risk. Methods: Follow-up studies were identified by search of PubMed and Embase databases published until May 26, 2019. A random-effect model or fixed-effect model was applied to pool the results according to the heterogeneity. Subgroup analyses according to the menopausal status, ethnic groups, cancer histopathological features, and study design characteristics. Results: Overall, seventeen follow-up studies with 602,195 women and 15,945 cases of breast cancer were included. Results of meta-analysis showed that MetS defined by the revised National Cholesterol Education Program’s Adults Treatment Panel III criteria was associated with significantly increased risk for breast cancer incidence (adjusted risk ratio [RR] = 1.15, p = 0.003). Subgroup analyses showed that MetS was associated with significantly increased risk of breast cancer in postmenopausal women (adjusted RR = 1.25, p < 0.001), but significantly reduced breast cancer risk in premenopausal women (adjusted RR = 0.82, p < 0.001). Further analyses showed that the association between MetS and increased risk of breast cancer were mainly evidenced from studies including Caucasian and Asian women, reporting invasive breast cancer, and of retrospective design. Conclusions: Menopausal status may affect the association between MetS and breast cancer incidence. Postmenopausal women with Mets are associated with increased risk of breast cancer.